A place for pragmatism in the current educational system in Poland in comparison to the American system of education - Czujko, Ewelina (Journal of Education Culture and Society, 2020)
Nowadays, when schools are closing and teachers are made redundant, a question arises whether the current educational system and the teaching methods or the knowledge and skills which people leave school with are adequate. Now, as never before, students and em-ployers realize how important practical skills are in the labor market. Where are schools and universities in meeting this need? Do schools answer the natural needs people have for self--development? Does the educational system stimulate development of individuals interests? Unfortunately, I think the answer to a lot of these questions would be negative. Yet, if so, it is time we fi nd a way to offer something more, not only to young people, but also to adults who want to explore the area of their interests by taking the trouble to obtain further degrees. One of the solutions to the urgent needs for the educational system is a pragmatic approach towards learning and teaching.